1971
DOI: 10.1002/cpt1971126897
|View full text |Cite
|
Sign up to set email alerts
|

The binding of sulfaphenazole to fetal, neonatal, and adult human plasma albumin

Abstract: Recently, Ganshorn and Kurz 5 reported that the plasma binding of the su1£onamide drugs, su1£amethoxidiazine and su1£ame-thoxine, was greater in adult plasma than in plasma from cord blood. Since the su1£on-amides are bound mainly to plasma albumin, l we investigated the interaction of sulfaphenazole with albumin isolated by starch block electrophoresis from cord plasma and from the plasma of neonates and adults. Our results show that sulfaphenazole has a lower affinity for plasma albumin isolated from cord an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
1

Year Published

1972
1972
1991
1991

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 2 publications
1
16
1
Order By: Relevance
“…In support of this, cord and adult albumin, isolated by a simple salting-out technique, were reported to differ in electrophoretic and chromatographic properties and to vary in resistance to alkali and proteolytic enzymes (5,6). However, authors of subsequent papers questioned the existence of a functionally immature albumin and attributed the reduced binding of newborn serum to competitive binding by increased concentrations of certain metabolites such as arachidonic acid and hematin (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…In support of this, cord and adult albumin, isolated by a simple salting-out technique, were reported to differ in electrophoretic and chromatographic properties and to vary in resistance to alkali and proteolytic enzymes (5,6). However, authors of subsequent papers questioned the existence of a functionally immature albumin and attributed the reduced binding of newborn serum to competitive binding by increased concentrations of certain metabolites such as arachidonic acid and hematin (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Since antimicrobial agents are frequently administered to such patients, an eluci dation of the interaction between antimicrobials and bilirubin is of potential clinical importance. Previous reports have shown that the binding of sulfaphenazole to albumin may be influenced by bilirubin (7). The present study is focused on how the protein binding of several antimicrobial agents in vitro is affected by unconjugated bilirubin.…”
mentioning
confidence: 99%
“…Several recent studies have indicated that numerous drugs are bound less extensively to plasma proteins of the newborn human infant than in plasma of the adult [2,6,8,12]. This phenomena has generally been attributed to lower albumin levels of the infant at birth and to competition for binding sites by endogenous ligands such as bilirubin, sex hormones and fatty acids.…”
Section: Introductionmentioning
confidence: 99%